Dealing More Effectively and Humanely with Illegal Drugs - Caulkins, Jonathan P. (Crime and justice, 2017)
Many judge the American criminal justice system to have largely failed in its drug enforcement role, and the justice system itself has suffered a loss of community support and internal morale as a consequence. Five principles should guide improvement of drug enforcement, including that drug enforcement be viewed as a preventive activity, whose main goal is reducing drug abuse and related harms, and it should be designed for sustainability. Six more specific proposals are, first, make marijuana enforcement a minor matter for police through decriminalization of possession or outright legalization; second, induce drug users who are under criminal justice supervision to refrain from drug use by imposing appropriate monitoring and graduated sanctions programs; third, expand opioid substitution therapy for heroin- and other opioid-using offenders; fourth, reduce the average severity of sentences for drug offenses, particularly for minor functionaries who are easily replaced; fifth, base sentence length on culpability, danger, and replaceability, not quantity possessed or number of prior convictions; and sixth, reduce prescription drug abuse by policing that reinforces regulatory efforts. Jointly these proposals would provide an evidence-informed approach that should both reduce America’s drug abuse problem and increase the perceived legitimacy of the criminal justice system.